Layanan Administrasi Kesiswaan di SMP Negeri 55 Palembang - Annur, Saipul; Sari, Delia Permata; Ibrahim, Ibrahim; Maulana, Dian (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze student administration services at SMP Negeri 55 Palembang, covering service processes, as well as supporting and inhibiting factors. The research employs a descriptive qualitative method with interviews, observations, and documentation. Informants include key and supporting participants, totaling 20 individuals. Key informants consist of the head of administration, administrative staff, and students. Supporting informants include vice principals, teachers, and parents. The data analysis techniques used include data reduction, data presentation, data verification, and conclusion drawing. Data validity was tested using source triangulation, technique triangulation, and time triangulation. The findings indicate that student administration services have been running effectively, supported by a digital system that minimizes errors in the administrative process. Administrative staff exhibit reliability, active responsiveness, and a high level of empathy in assisting students, parents, and teachers requiring help